Variation in Blood Glucose and Blood Pressure Distribution among Students of a Tertiary Institution in Port-Harcourt - S. O. Ojeka; T. G. Ibulubo; F. Saronee (Archives of Current Research International, 2021)
Introduction: Globally, reports on diabetes, hypertension and other cardiovascular diseases have shown to pose a major pitfall of health challenge, resulting in mortality especially among middle and low-income groups in developing countries. Aim: This research was therefore undertaken to determine the variation in blood glucose and blood pressure distribution among individual students of a tertiary institution in Port-Harcourt, Nigeria. Methodology: This is a randomized cross sectional observational study. 220 apparently healthy students (54 male and 166 female) of Rivers State College of Health Sciences and Management Technology (RIVSCOHSMAT), Port Harcourt were recruited into the study, Fasting blood glucose and blood pressure were determined using glucometer and sphygmomanometer respectively. Results: The results show the prevalence of prehypertension and hypertension as 8.2% and 10.5% respectively. The results revealed that 2.3% of the population was pre-diabetic with a higher prevalence in men (5.6%) compared to females (1.2%). Male subjects had significantly higher fasting blood sugar, systolic, diastolic and mean arterial blood pressure compared to the females (p<0.05). Conclusion: The study revealed gender differences in blood glucose homeostasis between women and men. More awareness is needed to encourage a healthier lifestyle to reduce the burden of diabetes and hypertension.